Nitric Oxide Synthase Inhibitor Improves De Novo and Long-Term l-DOPA-Induced Dyskinesia in Hemiparkinsonian Rats - Padovan-Neto, Fernando E.; Echeverry, Marcela B.; Chiavegatto, Silvana; Del Bel, Elaine (Frontiers in Systems Neuroscience, 2011)
Inhibitors of neuronal and endothelial nitric oxide synthase decrease l-3,4-dihidroxifenilalanine (L-DOPA)-induced dyskinesias in rodents. The mechanism of nitric oxide inhibitor action is unknown. The aims of the present study were to investigate the decrease of L-DOPA-induced abnormal involuntary movements in 6-hydroxydopamine (6-OHDA)-lesioned rats by nitric oxide inhibitors following either acute or chronic treatment. The primary findings of this study were that NG-nitro-L-Arginine, an inhibitor of endothelial and neuronal nitric oxide synthase, attenuated abnormal involuntary movements induced by chronic and acute L-DOPA. In contrast, rotational behavior was attenuated only after chronic L-DOPA. L-DOPA improved stepping test performance, and its chronic administration did not alter open field behavior. Our results indicated a correlation between apomorphine-induced rotation and the decrease in the number of adjusting steps performed with the contralateral forepaw in the 6-OHDA-lesioned rats.The 6-OHDA lesion and the L-DOPA treatment induced a bilateral increase (1.5 times) in the nNOS protein and nNOS mRNA in the striatum and in the frontal cortex. There was a parallel increase, bilaterally, of the FosB/ΔFosB, primarily in the ipsilateral striatum. The exception was in the contralateral striatum and the ipsilateral frontal cortex, where chronic L-DOPA treatment induced an increase of approximately 10 times the nNOS mRNA. Our results provided further evidence of an anti-dyskinetic effect of NOS inhibitor. The effect appeared under L-DOPA acute and chronic treatment. The L-DOPA treatment also revealed an over-expression of the neuronal NOS in the frontal cortex and striatum. Our results corroborated findings that L-DOPA-induced rotation differs between acute and chronic treatment. The effect of the NOS inhibitor conceivably relied on the L-DOPA structural modifications in the parkinsonian brain. Taken together, these data provided a rationale for further evaluati